Peran Inovasi Produk Dan Promosi Online Dalam Meningkatkan Penjualan UMKM - Sirait, Fransiska; Junita, Dina Rina; Arsiyanti, Deni (STIE Bina Karya, 2025)
The development of digital technology has driven significant changes in the marketing strategies implemented by Micro, Small, and Medium Enterprises. This study aims to analyze in depth the role of product innovation and online promotion in increasing sales. The research approach used is descriptive qualitative, with data collection techniques through in-depth interviews with several actors in the culinary and fashion sectors. The results of the study show that product innovation plays an important role in creating differentiation and increasing competitiveness in an increasingly competitive market. Meanwhile, online promotion through social media not only expands consumer reach but also builds customer interaction and trust in the brand. The combination of these two strategies has been proven to have a positive impact on increasing sales and business sustainability. This study confirms that the success of micro-businesses in the digital era is highly dependent on the ability of business actors to innovate continuously and utilize digital technology optimally as part of their marketing strategy.